2014
DOI: 10.5897/ajpp2013.3838
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance of the oxidant - antioxidant status by aspartame in the organs of immune system of Wistar albino rats

Abstract: Aspartame (L-aspartyl-L-phenylalanine methyl ester) is one of the most widely artificial sweeteners consumed in so many products worldwide in various countries which added to a large variety of food, most commonly found in low calorie beverages. On metabolism in humans and experimental animals, aspartame is rapidly and completely metabolized to aspartic acid (40%), phenylalanine (50%) and methanol (10%). Methanol, a toxic metabolite is primarily metabolized by oxidation to formaldehyde and then to formate; the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Oral aspartame (75 mg/kg body weight/day) consumption causes oxidative stress in brain 21 and its (40 mg/kg bw/day) consumption caused oxidative stress in brain, 22 liver and kidney, 23 and also in immune organs. 24 This inadequacy, combined with the general limited knowledge about the safety/potential toxigenic effects of substances widely present in the industrialized diet, motivated the design of the current study. However, little is known about the effects of aspartame on cytokine expression.…”
Section: Introductionmentioning
confidence: 99%
“…Oral aspartame (75 mg/kg body weight/day) consumption causes oxidative stress in brain 21 and its (40 mg/kg bw/day) consumption caused oxidative stress in brain, 22 liver and kidney, 23 and also in immune organs. 24 This inadequacy, combined with the general limited knowledge about the safety/potential toxigenic effects of substances widely present in the industrialized diet, motivated the design of the current study. However, little is known about the effects of aspartame on cytokine expression.…”
Section: Introductionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) play a role in elevating central and peripheral sympathetic activity by increasing nitric oxide production [31]. Our previous study showed that aspartame acts as a chemical stressor, alters the oxidative-antioxidative balance [10,11], increases oxidative stress, and depresses HRV [32]. When a person is exposed to a stressor, the autonomic nervous (ANS) system is triggered: the parasympathetic nervous system is suppressed, and the sympathetic nervous system is activated [24].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, based on previous studies, the ability of aspartame and its metabolites to alter the oxidative status of the cells via reactive oxygen species (ROS) generation and the modulation of intracellular antioxidant enzyme levels were investigated. Oral aspartame consumption at 75 mg/(kg bw/day) has been found to cause oxidative stress in the brain and liver [6,7], and oral aspartame consumption at 40 mg/(kg bw/day) has been found to cause oxidative stress in the brain [8], liver and kidney [9], and immune organs [10] and to alter immune response [11]. The inadequacy of past studies, combined with the general limited knowledge about the safety/potential toxigenic effects of substances widely present in the industrialized diet, motivated the design of this experiment.…”
Section: Introductionmentioning
confidence: 99%
“…Aspartame also stimulates the sympathetic nervous system by causing an increase in cortisol steroid levels in the adrenal glands via the hypothalamic-pituitary-adrenal (HPA) axis (Table 2) [93,94]. It also changes the composition of the gut microbiota [95,96].…”
Section: Behavioral Disordersmentioning
confidence: 99%